Bicornuate Uterus with Previous C-Section: A Case Report - Suparman, Erna (Jurnal Biomedik : JBM, 2021)
Abstract: Bicornuate uterus is a type of Mullerian duct malformation caused by incomplete fusion of fundal uterine cornu that leads to two connected uterine cavities and one cervix. The incidence of bicornuate uterus is estimated to be 0.1-0.6% and it is believed to account for 10% of all uterine anomalies. We reported a case of bicornuate uterus with previous cesarean sections in an expecting mother presented in labor during her 38-39 weeks of pregnancy. She had a history of two previous cesarean sections. Based on physical examination and transabdominal USG, the fetus was found in breech presentation. She was managed with another cesarean section. During the operation it was found that she had a bicornuate uterus. The main problems for this case were pregnancy with bad obstetric history, previous cesarean sections, breech presentation, and complications that could occur in future pregnancy. The patient was presented already in labor, so she was managed with emergency cesarean section to reduce the risk of uterine rupture. During the operation, she was found to have a bicornuate uterus. This proved that the cause of repeated breech presentation was one of the complications that could occur in pregnancy with bicornuate uterus. The most ideal management for this patient was elective cesarean section. In conclusion, uterine abnormalities are accompanied with uneventful outcomes such as preterm labour, fetal malpresentations, and even perinatal mortality. However, these anomalies may not be suspected before the occurrence of abortion or its complications. A high index of suspicion is needed to diagnose uterine abnormalities before the occurence of its complicationsKeywords: bicornuate uterus; breech presentation; pregnancy; Mullerian duct anomalies